STAT1/STAT3 Gain of Function and Mechanisms of Immune Dysregulation - Ayça Kıykım (Turkish Journal of Immunology)
The Janus kinase (JAK) and signal transducer and activator of transcription (STAT) signaling pathways are essential for maintaining prompt immune responses to various cytokines. Both loss- and gain-of-function mutations in the JAK and STAT molecules result in different disease profiles in inborn errors of immunity. The discovery of gain-of-function mutations in STAT1 and STAT3 expanded immunological investigations aimed at understanding both signaling pathways and their associated disorders. Both defects are distinct from loss-of-function mutations that lead to alterations in immune regulation. In this context, we wanted to take a look at both diseases and focus on the mechanisms.